Optimization of the Design an Ergonomic Multi-Function Oil Slicer - Mujiono; Sujianto (Journal Knowledge Industrial Engineering (JKIE), 2022)
The results of observations made by the research team at the corn emping home industry have its own uniqueness, namely corn that has been boiled then washed and fried, dried in the sun and fried which will become marning corn. In fact, it turns out that the frying of corn chips still uses manual tools, namely the slicing using an irek, so it takes a long time and cannot be optimal. Optimal in question is that the tool can be used in a number of fried foods, for example in marning corn chips, onion crackers, etc. by adjusting the speed. The purpose of designing an ergonomic tool in question is to design a tool that produces a work system using anthropometric measurements, while this research is focused on designing a multi-functional oil drainer with an ergonomic approach with results that are more effective, efficient, safe, comfortable and can increase productivity. The production this slicing machine uses a 0.50 hp electric motor with 1400 rpm rotation, the V-belt used is type A belt machine, no. 38 with a pulley component with a diameter of 2 inches for the sharft, the machine frame uses an angle iron profile frame with size of 40 mm x 40 mm x 3 mm capability of 5 kg marning corn chips.